PENGARUH KECERDASAN EMOSIONAL TERHADAP KETERLIBATAN KERJA DAN KOMITMEN ORGANISASIONAL DENGAN PERSEPSI POLITIK ORGANISASI SEBAGAI VARIABEL MODERASIPADA KARYAWAN PT. PLN (PERSERO) AREA BANDA ACEH - Nurul Ulfa, Nasrillah Anis (Departemen Manajemen, 2016)
This research is conducted to investigate the effect of Emotional Intelligence on Job Involvement and Organizational Commitment with Perceived Organization Politics as a Moderating Variable. The sample used in this research are employees of PT. PLN (Persero) Area Banda Aceh. The instrument of collecting data in this research is questionnaire. The sampling technique used in this study is Stratified random sampling. With a total of 107 questionnaires were distributed and just only 95 can be collected. Method of data analysis are Moderate Regression Analysis (MRA) which used as methods of analysis to determine the effect of all the variable involved. The result of this study indicate that Emotional Intelligence have significant effect on Job Involvement and Organizational Commitment. Perceived Organization Politics has significant effect on Job Involvement and Organizational Commitment. In addition abtained results that Perceived Politic Organization has moderated on the effect of Emotional Intelligence to Job Involvement and Organizational Commitment on employees PT. PLN (Persero) Area Banda Aceh. Keywords: Emotional Intelligence, Job Involvement, Organizational, Commitment, Perceived Organization Politics